HUBUNGAN PERILAKU MEROKOK, STATUS GIZI DAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN PENYAKIT ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS PEUDADA KECAMATAN PEUDADA KABUPATEN BIREUEN - Armiatin (Jurnal Cakrawala Ilmiah, 2023)
Background Behind : ARI disease is problem health to be attention world , WHO reports nearly 6 million child toddler die world , 16% of them caused by pneumonia which is wrong one manifestation from ISPA. Purpose Study this is for know connection behavior smoking, nutritional status and exclusive breastfeeding _ with incident ISPA disease in the Work Area Public health center Peudada Subdistrict Peudada Regency Bireuen Year 2022. Kind research used _ is study analytic with cross sectional approach ie approach where data collection for variable independent and variable dependent collected in one same time _ or in one period certain ( Sugiyon, 2018). whole mother whose child diagnosed with ARI by doctor in the Work Area Public health center Peudada on January-March in 2022 which amounts to 520 toddlers. Data collection using questionnaire. Technique taking sample used _ in study this is purposive sampling. Based on results calculation sample obtained 84 people. Results Study obtained exists connection behavior smoke with incidence of ARI, results calculation pvalue is 0.011, there is connection between nutritional status with incidence of ARI, results calculation pvalue is 0.041. There is a relationship Among exclusive breastfeeding _ with incidence of ARI, results calculation pvalue is 0.041. Suggestion: Expected officer health more active socialize activity form counseling contained health _ about education nor information about danger smoking, nutrition and importance exclusive breastfeeding _ so that knowledge Public more increase as wrong one effort countermeasures disease and death.